Pengaruh Pemberian Kulit Ari Biji Kedelai Hasil Fermentasi dengan Aspergillus niger sebagai Pengganti Jagung dan Bungkil Kedelai dalam Ransum terhadap Retensi Bahan Kering, Bahan Organik dan Serat Kasar pada Ayam Pedaging - Mairizal, Mairizal (Fakultas Peternakan Universitas Jambi, 2009)
The research on substitution of corn and soybean cake with fermented soybean husk by Aspergillus niger was done on 100 DOCs strains MB 202. Completely Randomizing Design (CRD) was used in five treatments: 0, 10, 20, 30 and 40% of fermented soybean husk by four replications. Observed variables were the retentions of dry matter, organic matter and crude fiber. Data were analyzed with analysis of variance continued by Duncan Multiple Range Test. The results showed that substitution of corn and soybeans cake with fermented soybean husk had no significant effect (P>0.05) on the retention of the dry matter but significantly (P<0.05) affected retentions of organic matter and crude fiber. In conclusion, the fermented soybeans husk can be used as a substitute for corn and soybean cake up to 40% of broiler feed.